The appreciation and criticism of the young Chinese Zhihu Netizens to ex-president Trump of the United States - Chen, Yawei; Ahamd, Abdul Muati Zamri; Mahamed, Mastura; Kasimon, Diyana (Redfame Publishing, 2022)
Since former U.S. President Trump took office, Chinese state media have generally painted a negative picture of him and formed a negative public opinion. However, in Chinese social media, Trump still enjoys a high reputation and has even gained a large number of supporters, including, of course, a large number of opponents. This article explored the popular evaluation of President Trump by young Zhihu netizens through a qualitative content analysis of a post on the Zhihu website, and analyzed the reasons for the formation of the opposing evaluations by netizens. The result showed that 43% of netizens positively evaluated Trump as the great president who saved the United States, while 40% condemned Trump as "The second Hoover." From a neutral point of view, Trump is seen as a president with first-class dreams but second-class political wisdom. Further analysis revealed that for netizens with positive comments, individualism, pragmatism, dissatisfaction with the social status quo, and the influence of the mode of public opinion confrontation are the main reasons why they praise Trump. Netizens who hold a negative evaluations are strongly influenced by China's traditional political culture and official public opinion, as well as the trend of the "rise of the East and decline of the West," which led them to follow the Chinese "Meritocracy Political Model" in evaluating Trump. This study revealed the current situation of ideological and value opposition among highly educated young in China.